2017
DOI: 10.1186/s13073-017-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cancer type from tumour DNA signatures

Abstract: BackgroundEstablishing the cancer type and site of origin is important in determining the most appropriate course of treatment for cancer patients. Patients with cancer of unknown primary, where the site of origin cannot be established from an examination of the metastatic cancer cells, typically have poor survival. Here, we evaluate the potential and limitations of utilising gene alteration data from tumour DNA to identify cancer types.MethodsUsing sequenced tumour DNA downloaded via the cBioPortal for Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…In our study, we were able to obtain reasonable accuracy performances using the germline matrix only as an input. This suggests that germline variation may be more important than previously reported based on prior methods (15). More specifically, we found that breast cancer and colorectal cancer have the best performance using only germline information, suggesting that these two cancers probably confers higher heritability compared to others.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In our study, we were able to obtain reasonable accuracy performances using the germline matrix only as an input. This suggests that germline variation may be more important than previously reported based on prior methods (15). More specifically, we found that breast cancer and colorectal cancer have the best performance using only germline information, suggesting that these two cancers probably confers higher heritability compared to others.…”
Section: Discussionsupporting
confidence: 44%
“…To help improve cancer diagnosis and targeted therapies, cancer type classification methods are continually being upgraded. Traditionally, the majority of classification methods based on DNA sequencing data has relied on studying single point somatic mutations with various regression models (15,39,40). Mutations involving insertions and deletions as well as germline mutations have been largely ignored due to the high dimensionality problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in the area of DNA-based tumour type identification has used targeted gene panel 40 and whole exome [41][42][43] sequencing strategies. The targeted gene-based approach described in Tothill 40 is able to discriminate a handful of tumour types that have distinctive driver gene profiles, and can identify known therapeutic response biomarkers, but does not have broader applicability to the problem of tumour typing.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies involving DNA mutations have used mutations as individual variables. Soh et al [20] used somatic mutations derived from 100 representative genes to distinguish cancer types and the results concluded that using somatic point mutations alone as individual variables was not sufficient to classify cancer types. Despite the fact that mutations in many genes have been identified in cancer, it is not yet understood how these genes cumulatively interact in the development and progression of cancer.…”
Section: Related Workmentioning
confidence: 99%